2019
DOI: 10.1002/adom.201900544
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐Wave Pumped Perovskite Lasers

Abstract: Continuous‐wave (CW) operated lasers are regarded as a stepping stone to the development of electrically driven lasers and crucial for practical application in high‐density integrated optoelectronic devices. Recently, metallic halide perovskites are demonstrated as excellent gain materials for CW lasers owing to their large optical absorption coefficient, low defect density, long diffusion length, and suppressed Auger recombination rate. Here, the latest research advances on CW pumped perovskite lasers are rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…The as-demonstrated net optical gain coefficient of CsFAMA/NMA 0.8 is the highest value among perovskite materials, and it is nearly one order of magnitude higher than that of the solution-process CsPbBr 3 thin films, and three times higher than that of single-crystalline CsPbBr 3 nanocrystal films (Table S1 and S2, Supporting Information). [22,23,46] Notably, the NMA cation could also optimize the ASE performance of pure FAPbBr 3 film with a lower threshold and enhanced net optical gain (Figure S17, Supporting Information). Further, the loss coefficient α of the CsFAMA/NMA 0.8 film was also measured by detecting the ASE intensity as a function of the distance.…”
Section: (4 Of 8)mentioning
confidence: 99%
See 1 more Smart Citation
“…The as-demonstrated net optical gain coefficient of CsFAMA/NMA 0.8 is the highest value among perovskite materials, and it is nearly one order of magnitude higher than that of the solution-process CsPbBr 3 thin films, and three times higher than that of single-crystalline CsPbBr 3 nanocrystal films (Table S1 and S2, Supporting Information). [22,23,46] Notably, the NMA cation could also optimize the ASE performance of pure FAPbBr 3 film with a lower threshold and enhanced net optical gain (Figure S17, Supporting Information). Further, the loss coefficient α of the CsFAMA/NMA 0.8 film was also measured by detecting the ASE intensity as a function of the distance.…”
Section: (4 Of 8)mentioning
confidence: 99%
“…[11][12][13][14] So far, several studies have reported on the usage of low-threshold photoluminescence (PL) lasing in single-crystalline bulk and low-dimensional CsPbBr 3 . [15][16][17][18][19][20][21][22][23] However, the mass fabrication and integration of these structures, and thus lasing devices, are very challenging for practical optoelectronic applications. Although solution-processed spin-coated thin films could resolve this problem, the amplified spontaneous emission (ASE)/lasing devices of these films suffer from high threshold owing to poor crystallinity as a result of low solubility of cesium bromide (<<0.1 mol L −1 ) and insufficient optical gain.…”
Section: Introductionmentioning
confidence: 99%
“…Lead halide perovskite nanocrystals (NCs) have garnered recent attention because of their unique versatility as laser gain materials, such as high photoluminescence quantum yields (PLQYs), an easy synthesis process, and a tunable bandgap with different elements . The molecular formula of the perovskite crystal can be expressed as ABX 3 , where cation A and cation B are bound to anion X.…”
Section: Perovskite Qdsmentioning
confidence: 99%
“…Miniaturized lasers have gained increasing interest owing to their applications in chemical and biological sensing, [1][2][3][4] laser display, [5][6][7] imaging 8 , and on-chip optical interconnects [9][10][11][12] . Wavelength-tuneable lasers with the capability of delivering intense coherent light signals across broad spectral range open up particularly interesting opportunities for highly integrated photonic devices.…”
Section: Introductionmentioning
confidence: 99%